Efektifitas Teknik Counterpressure Untuk Mengurangi Rasa Nyeri Persalinan Kala I Di Praktik Mandiri Bidan Sutra Des Kelissa Kota Bekasi Tahun 2022 - Khoiriah, Restu; Wahyuni, Dwi Reza (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Introduction: Labor is the process of opening and thinning the cervix, as well as uterine contractions, and the fetus descending into the birth canal, causing pain in labor. Labor pain is a physiological process as many as 12%-67% of women feel worried about the pain that will be experienced during labor. Efforts to reduce labor pain are counterpressure techniques. Research objectives: to determine the effectiveness of counterpressure techniques to reduce pain in the first stage of labor in the Midwife Independent Practice of the Sutra Des Kelissa Kel. West Bekasi District Officer in 2022. Methods: This study used a quasi-experimental method with a two-Group posttest only design which was divided into two groups, namely the control group and the intervention group. The sampling technique in this study used a total sampling of 30 mothers giving birth in the first stage of the active phase and each 15 people in the control group and 15 people in the intervention group. Data were collected using observation sheets and analyzed using the Mann Withney U test. Results: The study showed that the counterpressure technique was more effective in reducing the level of pain in active phase maternity mothers as indicated by the p-value equal to (0.005) less than 0.05, meaning that there was a difference in pain scale between the intervention group and the control group. Conclusion: The counterpressure technique is a good alternative that needs to be recommended to reduce pain intensity in active phase I birth mothers